Conducting the Needs Assessment #9: The Nominal Group Technique - Mary Bammer; Matthew Benge; Laura Warner (EDIS)
This ninth publication in the Conducting the Needs Assessment series provides an overview of using the nominal group technique (NGT) to conduct a needs assessment. This document defines the scenarios in which the NGT is suitable, describes the steps involved in conducting the NGT, and provides examples of the use of this technique in Extension. Written by Mary Bammer, Matt Benge, and Laura Warner, and published by the UF/IFAS Department of Agricultural Education and Communication; 5 pp.